Finding the 'Herstorical' Narrative in Angie Thomas's The Hate U Give. Issue 1 (2nd January 2020) - Levin, Adam
Abstract: In this article I use Angie Thomas's popular young-adult novel The Hate U Give as a lens through which to explore how young adult fiction, produced by African American writers, can serve to facilitate social activism and change. In the novel, Thomas's Black teenage protagonist, Starr Carter, undergoes a transformation from victim and witness to activist after she sees her Black male friend murdered by a white police officer. As I will demonstrate, the novel is guided and shaped by the ideologies of the Black Lives Matter Movement as it explores the complexities of Blackness in both post-racial and communal spaces. By drawing on these ideologies and employing the perspective of a Black teenage girl, Thomas engages her Black female readers in a readerly process in which they reflect on how Starr's narrative relates to their own lives. In doing so, I argue, she encourages these readers to explore ways in which their own narratives can be used to instigate social activism and change.